TRPML1: The Ca(2+)retaker of the lysosome. (January 2018) - Di Paola, Simone; Scotto-Rosato, Anna; Medina, Diego Luis
Graphical abstract: Highlights: Release of Ca 2+ from the lysosome is emerging as an important signalling mechanism to modulate autophagy and lysosomal biogenesis. The lysosomal non selective cation channel TRPML1 plays a major role in such signaling, being involved in vesicular trafficking, lysosomal exocytosis and autophagy. Mutations in human TRPML1 gene cause mucolipidosis type IV, a severe neurological lysosomal storage disorder. In this review, we provide an overview of the most recent studies aimed to characterize the role of TRPML1 on lysosomal function in health and disease. Abstract: Efficient functioning of lysosome is necessary to ensure the correct performance of a variety of intracellular processes such as degradation of cargoes coming from the endocytic and autophagic pathways, recycling of organelles, and signaling mechanisms involved in cellular adaptation to nutrient availability. Mutations in lysosomal genes lead to more than 50 lysosomal storage disorders (LSDs). Among them, mutations in the gene encoding TRPML1 ( MCOLN1 ) cause Mucolipidosis type IV (MLIV), a recessive LSD characterized by neurodegeneration, psychomotor retardation, ophthalmologic defects and achlorhydria. At the cellular level, MLIV patient fibroblasts show enlargement and engulfment of the late endo -lysosomal compartment, autophagy impairment, and accumulation of lipids and glycosaminoglycans. TRPML1 is the most extensively studied member of a small family of genes that also includes TRPML2 and TRPML3, and it has been found to participate in vesicular trafficking, lipid and ion homeostasis, and autophagy. In this review we will provide an update on the latest and more novel findings related to the functions of TRPMLs, with particular focus on the emerging role of TRPML1 and lysosomal calcium signaling in autophagy. Moreover, we will also discuss new potential therapeutic approaches for MLIV and LSDs based on the modulation of TRPML1-mediated signaling.